Disruptive Seeds and transformation pathways for Guatemala's food system - Rutting, Lucas; Veeger, Marieke (CGIAR Initiative on Climate Resilience, 2022)
This working paper describes a bottom-up approach to transformative change, the Disruptive Seeds approach. It is applied as part of ClimBeR’s Policy Pathways research (Work Package 3) in Guatemala and focuses on the potential of sustainable niche initiatives (i.e., disruptive seeds) that have the potential to grow in terms of impact. The objective of the project is to develop pathways for transformation of Guatemala’s food system based on identified seed initiatives. Seeds, in this regard, refer to “initiatives (social, technological, economic, or social–ecological ways of thinking or doing) that exist, at least in prototype form, and that represent a diversity of worldviews, values, and regions, but are not currently dominant in the world” (Bennett et al. 2016:442) and “real-world agents of current social-ecological transformation that are currently marginal, but have the potential to grow in impact” (Raudsepp-Hearne et al. 2019:606). The Seeds approach offers a novel, bottom-up method of transformative scenario development based on real- world initiatives (Bennett et al. 2016; Pereira et al. 2018).